Fluid Inclusions and H–O–C–S–Pb Isotopic Systematics of the Jinba Gold Deposit, NW China: Implications for Ore Genesis - Li, Shun-Da; Chen, Chuan; Gao, Ling-Ling; Xia, Fang; Zhang, Xue-Bing; Wang, Ke-Yong (Frontiers in Earth Science, 2021)
The Jinba gold deposit is located in the Maerkakuli Shear Zone of the south Altay Orogenic Belt, NE China. Mineralization types are classified as altered rock– and quartz vein–type. Orebodies occur as veins or lenses controlled by NW–trending faults, and are hosted in phyllite (Ashele formation) and plagiogranite (Habahe Pluton). Three paragenetic stages were identified: early quartz–pyrite–gold (Stage 1), middle quartz–chalcopyrite (Stage 2), and late calcite–quartz–galena–sphalerite (Stage 3). Fluid inclusions (FIs) within the deposit are liquid–rich aqueous (LV–type), vapor–rich aqueous (VL–type), carbonic–aqueous (LC–type), and purely carbonic (C–type) FIs. Homogenization temperatures for stages 1–3 FIs were 373–406°C, 315–345°C, and 237–265°C, respectively. Fluid salinities for stages 1–3 were 2.1–13.6 wt.%, 3.2–6.1 wt.% and 3.9–6.0 wt.% NaCl equivalent, respectively. The ore–forming fluids evolved from a CO2–NaCl–H2O±CH4 to a NaCl–H2O system from stage 1 to 3. Oxygen, hydrogen, and carbon isotopic data (δ18Ofluid=1.7‰ to 8.1‰, δDfluid= –104.1‰ to –91.7‰, δ13Cfluid= –0.4‰ to 6.3‰) indicate that ore–forming fluids were metamorphic hydrothermal origin with the addition of a late meteoric fluid. Sulfur and lead isotope data for pyrite (δ34Spy= 3.3‰ to 5.3‰, 206Pb/204Pb= 17.912.3–18.495, 207Pb/204Pb= 15.564–15.590, 208Pb/204Pb= 37.813–38.422) show that the ore–forming materials were mainly derived from diorite and the Ashele Formation. Mineralization, FIs, and isotope studies demonstrate that the Jinba deposit is an orogenic gold deposit.